Assessment of financial development of countries based on the matrix of financial assets - Galina Gospodarchuk; Elena Zeleneva (Economies, 2022)
Building an adequate system of indicators to assess the financial development of countries and its practical application can improve the robustness and effectiveness of government decision-making. This paper aims to create such a system. The study used the methods of structured system, comparative, matrix, and gap analysis. The key outcome of the study is a matrix system of indicators for assessing the financial development of countries. This indicator system is based on a matrix of all financial assets. Elements of the matrix of financial assets were calculated in relation to the population and used as indicators of the level of financial development of countries as a whole and in the context of financial instruments and sectors of the economy. Simultaneous recording of financial assets across the entire range of financial instruments and sectors of the economy, as well as their interrelations, is a relatively new direction for financial development assessment. The study produced criteria for the qualitative assessment of the level of the financial development of countries. Testing of the developed matrix system of indicators and criteria for financial development was carried out on current and potential members of OECD (OECD+) for the period 2018-2019. As part of the testing, the level of financial development of the analyzed countries was calculated, their ranking was gauged, and international positions were determined. A structural analysis of the financial development of OECD+ countries in terms of types of financial assets (instruments) and sectors of the economy was carried out. Promising areas of Italy's financial development have been identified. The test results confirmed that the matrix system of indicators and the developed criteria are an objective and convenient tool for assessing the level of financial development of countries. Their use makes it possible to increase the complexity and quality of the analysis of financial development, and it also forms a platform for making evidence-based and effective decisions in the development of national strategic documents.
Keywords: 330; financial development; financial development analysis; financial development indicators; financial development strategy